2019
DOI: 10.1302/0301-620x.101b1.bjj-2018-0554.r1
|View full text |Cite
|
Sign up to set email alerts
|

Should postoperative haemoglobin and potassium levels be checked routinely following blood-conserving primary total joint arthroplasty?

Abstract: Aims Despite declining frequency of blood transfusion and electrolyte supplementation following total joint arthroplasty, postoperative blood analyses are still routinely ordered for these patients. This study aimed to determine the rate of blood transfusion and electrolyte restoration in arthroplasty patients treated with a perioperative blood conservation protocol and to identify risk factors that would predict the need for transfusion and electrolyte supplementation. Patients and Methods Patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 38 publications
2
38
3
1
Order By: Relevance
“…Lin et al [10] reported that the incidence of abnormal electrolytes was low and the predictive value was small, and 0.92% of the patients undergo ing lumbar spinal surgery were diagnosed with hypokalaemia required postoperative clinical treatment. Likewise, Greco et al [14] demonstrated an incidence as great as 15.5% for patients who were provided electrolyte supplementation after total joint arthroplasty, and con rmed that preoperative potassium level associated with required postoperative clinical treatment with a threshold identi ed at a preoperative potassium level of 4mmol/L. In line with previous studies, we found that 3.55% of patients required potassium supplementation after HTO surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Lin et al [10] reported that the incidence of abnormal electrolytes was low and the predictive value was small, and 0.92% of the patients undergo ing lumbar spinal surgery were diagnosed with hypokalaemia required postoperative clinical treatment. Likewise, Greco et al [14] demonstrated an incidence as great as 15.5% for patients who were provided electrolyte supplementation after total joint arthroplasty, and con rmed that preoperative potassium level associated with required postoperative clinical treatment with a threshold identi ed at a preoperative potassium level of 4mmol/L. In line with previous studies, we found that 3.55% of patients required potassium supplementation after HTO surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Given the high volume, optimising investigation approaches may provide substantial cost savings even when the percentage of overall cost reduction is small. Recent studies have identi ed examples of ine cient routine investigations, including radiographs and blood tests, during post-arthroplasty care in tertiary centres in USA and in China (5)(6)(7)(8)(9)(10)(11). However, only one similar study has been conducted in Australia, investigating the utility of week-one radiographs postarthroplasty (4).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Given the high volume, optimising investigation approaches may provide substantial cost savings even when the percentage of overall cost reduction is small. Recent studies have identi ed examples of ine cient routine investigations, including radiographs and blood tests, during post-arthroplasty care in tertiary centres in USA and in China (5)(6)(7)(8)(9)(10)(11). In Australia, only one similar study has been conducted; it found that routine post-operative radiographs did not alter inpatient management of any patients, despite 23% having atypical radiographic ndings in that cohort (4).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Post-operative investigations, which are used by clinicians to detect complications, can impose substantial burden both nancially on the health system and physically on the patient (3). Recent studies have questioned investigation practices following total hip or total knee arthroplasty, and they have identi ed existing cost-ine ciency at individual institutions (4)(5)(6)(7)(8)(9)(10)(11). However, a general lack of knowledge on current practices greatly limits the applicability of such ndings.…”
Section: Introductionmentioning
confidence: 99%